Selenium-Enriched Lactobacillus acidophilus Ameliorates Dextran Sulfate Sodium-Induced Chronic Colitis in Mice by Regulating Inflammatory Cytokines and Intestinal Microbiota - Wu, Zeyu; Pan, Dan; Jiang, Min; Sang, Lixuan; Chang, Bing (Frontiers in Medicine, 2021)
AIM To evaluate the effect of Se-enriched Lactobacillus acidophilus on DSS-induced colitis in mice. METHODS Mice were randomly divided into 4 groups: a control group, a control + Se-enriched L. acidophilus group, a chronic colitis group, and a chronic colitis + Se-enriched L. acidophilus group (n=10 each group). The mice were sacrificed on the 26th day. The disease activity index, survival rates, and histological injury score were determined. Cytokines produced by LPL cells, the concentrations of serum and colon tissue Se and the mouse intestinal microbiota were evaluated. RESULTS Se-enriched L. acidophilus can improve histological injury and the disease activity index in mice with chronic colitis and reduce IL-1β, IL-6, IL-12p70, TNF-α, IL-23, IFN-γ, IL-17A, and IL-21 (P<0.05) and increase IL-10 (P<0.05) expression levels. Moreover, Se-enriched L. acidophilus can increase the β diversity of intestinal microbiota in mice with chronic colitis, significantly reduce the relative abundance of Lactobacillus and Romboutsia (P<0.05), and significantly increase the relative abundance of Parasutterella (P<0.05). CONCLUSIONS Se-enriched L. acidophilus can improve DSS-induced chronic colitis by regulating inflammatory cytokines and intestinal microbiota.